A proton-responsive ligand becomes a dimetal linker for multisubstrate assembly via nitrate deoxygenation. Issue 22 (18th February 2021) - Cabelof, Alyssa C.; Carta, Veronica; Caulton, Kenneth G.
Abstract : A bidentate pyrazolylpyridine ligand (HL) was installed on divalent nickel to give [(HL)2 Ni(NO3 )]NO3 . This species is reacted with TMS2 Pz to simultaneously reduce one of the nitrate anions and deprotonate one of the ligands. Abstract : A bidentate pyrazolylpyridine ligand (HL) was installed on divalent nickel to give [(HL)2 Ni(NO3 )]NO3 . This compound reacts with a bis-silylated heterocycle, 1, 4-bis-(trimethylsilyl)-1, 4-diaza-2, 5-cyclohexadiene (TMS2 Pz) to simultaneously reduce one of the nitrate ligands and deprotonate one of the HL ligands, giving octahedral (HL)(L − )Ni(NO3 ). The mononitrate species formed is then further reacted with TMS2 Pz to doubly deoxygenate nitrate and form [(L − )Ni(NO)]2, dimeric via bridging pyrazolate with bent nitrosyl ligands, representing a two-electron reduction of coordinated nitrate. Independent synthesis of a dimeric species [(L − )Ni(Br)]2 is reported and effectively assembles two metals with better atom economy.